2004
DOI: 10.4049/jimmunol.172.10.6144
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the SH2D2A Gene Is Dependent on a Cyclic Adenosine 5′-Monophosphate-Responsive Element in the Proximal SH2D2A Promoter

Abstract: The SH2D2A gene, encoding the T cell-specific adapter protein (TSAd), is rapidly induced in activated T cells. In this study we investigate the regulation of the SH2D2A gene in Jurkat T cells and in primary T cells. Reporter gene assays demonstrated that the proximal 1-kb SH2D2A promoter was constitutively active in Jurkat TAg T cells and, to a lesser extent, in K562 myeloid cells, Reh B cells, and 293T fibroblast cells. The minimal SH2D2A promoter was located between position −236 and −93 bp from the first co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…We previously identified two single-nucleotide polymorphisms (SNPs) in the 1-kb fragment of the SH2D2A promoter upstream of the first ATG, which were only present on chromosomes carrying the GA 16 allele. 6 Three SNPs in intron 2 5 were found not to be in LD with the GA repeats examined in this study (Dai and Spurkland, unpublished results). A number of other SNPs in the SH2D2A gene have now also been identified (http://www.ncbi.nlm.nih.gov/SNP/ snp_ref.cgi?locusId ¼ 9047).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…We previously identified two single-nucleotide polymorphisms (SNPs) in the 1-kb fragment of the SH2D2A promoter upstream of the first ATG, which were only present on chromosomes carrying the GA 16 allele. 6 Three SNPs in intron 2 5 were found not to be in LD with the GA repeats examined in this study (Dai and Spurkland, unpublished results). A number of other SNPs in the SH2D2A gene have now also been identified (http://www.ncbi.nlm.nih.gov/SNP/ snp_ref.cgi?locusId ¼ 9047).…”
mentioning
confidence: 65%
“…5 Initial analysis of the SH2D2A promoter identified the minimal promoter to be located proximal to position À236 upstream of the first coding ATG, whereas a putative silencer element was identified in the region encompassed by position À500 to À310, thus including the GA repeat. 6 We previously showed that 'short' alleles of the GA repeat in the SH2D2A promoter conferred lower expression of TSAd in activated CD4 T cells compared to long alleles. Hence, individuals being homozygous for 'short' alleles of this GA repeat in the SH2D2A gene promoter display reduced expression of TSAd in activated T cells.…”
mentioning
confidence: 97%
“…A key to understand the biological role of TSAd in T cells is probably its characterstic pattern of expression, since it is not expressed in naive resting T cells, but is rapidly induced upon stimulation of T cells [3,9,12,32]. This implies that whatever biological role TSAd serves in T cell signaling, it may not be involved in the first minutes or hours of signaling in naive T cells, since it is not present until at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…The possible effect of TSAd on proximal T cell activation is of particular interest since TSAd is not expressed in naive resting T cells, but is rapidly induced after T cell activation [3,12,13]. Jurkat T cells, which have been instrumental for development of the TCR signaling paradigm [14], do not consistently express TSAd [3,13] (Mark Nachtigal, personal communication), indicating that TSAd is not essential for T cell activation to occur.…”
Section: Introductionmentioning
confidence: 99%
“…In peripheral T cells, expression of the T cell-specific adapter protein (TSAd), encoded by the SH2D2A gene, is rapidly induced upon T cell activation (12)(13)(14)(15). TSAd (or Lad/RIBP (Lck adapter molecule/Rlk-Itk-binding protein)) interacts with a number of intracellular signaling molecules expressed in T cells, including the tyrosine kinases Lck (16 -18) and Itk (19), the serine/threonine kinase MEKK2 (20), the GTP exchange factor RasGAP (21), the adapter protein Grb2 (22), and the molecular chaperone valosinecontaining protein, VCP (23).…”
Section: Activation Of T Cells Through T Cell Receptor (Tcr)mentioning
confidence: 99%